A novel missense variant in the L2HGDH gene in a cat with L‐2‐hydroxyglutaric aciduria and multicystic cerebral lesions. (7th March 2023) - Christen, Matthias; Gonzalo‐Nadal, Veronica; Kaczmarska, Adriana; Dyrka, Magdalena; Guevar, Julien; Jagannathan, Vidhya; Leeb, Tosso; Gutierrez‐Quintana, Rodrigo
Abstract: Case Description: A 9‐month‐old intact male domestic shorthair cat was evaluated for increasing frequency of generalized tonic‐clonic seizures. Clinical Findings: The cat was reported to have had episodes of circling between the seizures. Upon examination, the cat had bilateral inconsistent menace response but otherwise normal physical and neurological examinations. Diagnostics: Magnetic resonance imaging (MRI) of the brain identified multifocal, small, rounded intra‐axial lesions within the subcortical white matter containing fluid with similar characteristics as cerebrospinal fluid. Evaluation of urine organic acids showed increased excretion of 2‐hydroxyglutaric acid. An XM_023255678.2:c.397C>T nonsense variant in the L2HGDH gene encoding L‐2‐hydroxyglutarate dehydrogenase was identified using whole genome sequencing. Treatment and Outcome: Levetiracetam treatment was initiated at 20 mg/kg PO q8h, but the cat died after a seizure 10 days later. Clinical Relevance: We report the second pathogenic gene variant in L‐2‐hydroxyglutaric aciduria in cats and describe for the first time multicystic cerebral lesions on MRI.